Colonic Transendoscopic Enteral Tubing: Route for a Novel, Safe, and Convenient Delivery of Washed Microbiota Transplantation in Children - Min Zhong; Heena Buch; Quan Wen; Chuyan Long; Bota Cui; Faming Zhang (Gastroenterology Research and Practice)
Aim. Colonic transendoscopic enteral tubing (TET) has been used for delivering fecal microbiota transplantation by washed preparation since 2015, which was recently named as washed microbiota transplantation (WMT). However, there are few reports available regarding the feasibility and safety of these studies in low-age population. This study is aimed at evaluating the safety, feasibility, and value of colonic TET in 3-7 years old children. Methods. All patients aged 3-7 years who underwent colonic TET in our center for WMT or medication were prospectively evaluated. The feasibility and safety of TET were evaluated. A questionnaire was completed by the children’s parents to evaluate the children’s response to the colonic TET as well as the parent’s satisfaction. Results. Forty-seven children were included (mean age 5 years). TET was implemented into the colon of all the patients, and the success rate of the procedure was 100%. The median retention time of TET tube within the colon was 6 (IQR 5-7) days in 45 patients with tube falling out spontaneously, and the maximum retention time was up to 21 days. Multivariate analysis demonstrated that endoscopic clip number (P=0.009) was an independent contributing factor for the retaining time of tube. With increase in the number of large clips, the retention time of TET tube was prolonged. No discomfort was reported during injection of the microbiota or medication suspension through the TET tube. During the follow-up, no severe adverse events were observed. All children’s parents were satisfied with TET. Interestingly, the proportion of children’s parents choosing TET as the delivery way of WMT increased from 29.79% before to 70.21% after TET (P<0.001). Conclusions. This study, for the first time, demonstrates that colonic TET is a novel, safe, and convenient colonic delivery way for WMT and medication in children aged 3-7 years.